Right coronary artery perforation extending to the coronary sinus of Valsalva during percutaneous intervention successfully sealed with polytetrafluoroethylene-covered stent: a case report - Sahela Nasrin; Fathima Aaysha Cader; M. Maksumul Haq; Md. Rezaul Karim (BMC Research Notes, 2017)
Abstract Background Right coronary artery perforation extending to the sinus of Valsalva is a rare and potentially fatal complication of percutaneous coronary intervention. There are no definite guidelines on the management strategies for such complications. Treatment modality depends on the patient’s haemodynamic stability and the extent of aortic involvement. Polytetrafluoroethylene-covered stents have emerged as a revolutionary strategy, enabling efficient endovascular repair of the entry port of such dissections, particularly the coronary ostia, and obviating the need for high-risk emergent surgical intervention. Case presentation A 60 year old Bangladeshi gentleman underwent a coronary angiogram following a prior inferior ST elevation myocardial infarction (MI), 1 month previously. Coronary angiography done via right radial approach using 5 FR TIG catheter showed diffuse mid RCA disease with maximum 90% stenosis. Angioplasty of the RCA was planned. The RCA was cannulated with a 6-French JR 3.5 guiding catheter (USA). The lesion was crossed by a 0.014 inch guide wire and stented with a 2.75 × 38 mm novolimus-eluting DESyne stent, after predilatation. Immediately after stenting, a Type II perforation was observed in the ostial RCA, which progressed into the right coronary sinus of Valsalva. As the patient was haemodynamically stable with no ischaemia on ECG, we attempted to seal the ostial RCA with bare metal stents. Two successive bare metal stents failed to seal the aorto-coronary dissection. Ultimately, a 3.0 × 19 mm polytetrafluoroethylene-covered stent was deployed to seal the entry port in the ostial RCA, yielding a satisfactory angiographic result with only minimal contrast staining limited to the right sinus of Valsalva. The patient was closely monitored and discharged on dual antiplatelet therapy comprising of aspirin and prasugrel. He remained asymptomatic and with follow up echocardiograms showing no pericardial effusion nor extension of the dissection. Conclusions The polytetrafluoroethylene-covered stent provides a safe and effective means of sealing iatrogenic aorto-coronary dissections complicated by Ellis type II or II perforations, thus avoiding emergency surgery. However, as they are associated with increased incidence of stent thrombosis, an efficient and prolonged post-PCI antiplatelet regimen is recommended.